2008
DOI: 10.1002/cncr.23785
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of cytokine levels in newly diagnosed acute myeloid leukemia and high‐risk myelodysplastic syndromes

Abstract: BACKGROUND.Tumor necrosis factor (TNF)‐α and other cytokines are involved in the pathogenesis of acute myeloid leukemia (AML) and high‐risk myelodysplastic syndromes (MDS), but their prognostic significance in these diseases is unknown. In the current study, the authors assessed the association between serum levels of various cytokines and clinical outcomes in patients with untreated AML or high‐risk MDS.METHODS.Serum levels of TNF‐α, interleukin (IL)‐1 receptor antagonist, IL‐6, IL‐10, and endostatin were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 31 publications
4
94
2
2
Order By: Relevance
“…This is in line with findings that many ligands of the TNF family mediate bidirectional signals (33) and with reports that RANKL alters cytokine production of T cells and CLL cells (19,34). The cytokines that we found to be induced by RANKL signaling into AML cells are known to act as autocrine/paracrine growth and survival factors in AML and are, at least in part, associated with development and progression of the disease (35,36). Notably, RANKL signaling did not always induce release of the same cytokines with all RANKL-positive patient samples.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with findings that many ligands of the TNF family mediate bidirectional signals (33) and with reports that RANKL alters cytokine production of T cells and CLL cells (19,34). The cytokines that we found to be induced by RANKL signaling into AML cells are known to act as autocrine/paracrine growth and survival factors in AML and are, at least in part, associated with development and progression of the disease (35,36). Notably, RANKL signaling did not always induce release of the same cytokines with all RANKL-positive patient samples.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, primary AML cells of 10 different patients were cultured alone, on isotype control or immobilized RANK-Ig, which enables RANKL multimerization. Subsequent analysis by ELISA revealed that RANKL signaling significantly (all p , 0.05, MannWhitney U test) enhanced the release of TNF, IL-6, IL-8, and IL-10, which are associated with AML pathophysiology (35,36), into the culture supernatants ( Fig. 2A).…”
Section: Expression Of Rankl In Amlmentioning
confidence: 94%
“…9 Previous reports showed that serum levels of inflammatory cytokines or chemokines in AML patients may represent a prognostic factor and correlate with the clinical outcome. 10,11 In this context, we have previously shown that IL-8 may accelerate in vitro CD34 + cell differentiation towards CD161 + CD56 + (NK) cells, thus suggesting that cytokines or chemokines, released during an inflammatory process, may influence NK-cell differentiation. 4 In the present study, in order to address the question as to whether AML blasts may affect NK-cell development, we performed co-cultures of umbilical cord blood (UCB)-CD34 + cells in the absence [control (CTR)] or in the presence of fresh leukemia blasts belonging to different FAB categories.…”
Section: -5mentioning
confidence: 98%
“…The knowledge gained from multi-analytical determination of cytokines and adhesion molecules could allow better diagnosis and management of hematological malignancies, since cytokines or their receptors may also represent a target for specific anticancer therapy at the molecular level. Recently, some studies reported the possible diagnostic and prognostic use of cytokine levels in newly diagnosed AML and myelodysplastic syndromes [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%